Contra o purismo epistêmico: a infiltração pragmática de Jeremy Fantl e Matthew McGrath - Ruivo, José Leonardo Annunziato (2013)
Recently some authors have defended a tendency in epistemology called Pragmatic Encroachment. Such authors propose to deny the thesis of epistemic purism: two subjects have the same epistemic strength if they are in the same position to know that p - where epistemic strength is determined by the relevant dimensions to truth of p. For that the encroachers will assume: (i) to know p some pragmatic condition must be satisfied or to satisfy a pragmatic condition one should know p; and, (ii) knowledge varies with pragmatic factors. In this dissertation we will discuss the arguments of Jeremy Fantl and Matthew McGrath in defense of the pragmatic encroachment, evaluating their limits and potential.